Overview of Genetic Epidemiology - Thomas, Duncan C. (Statistical Methods in Genetic Epidemiology, 2004)
Genetic epidemiology is the study of the joint action of genes and environmental factors in causing disease in human populations and their patterns of inheritance in families (Last, 1993; Morton, 1982; Neel, 1984; Rao, 1985; Thomas, 2000a). Many other disciplines also address aspects of this same overall objective—human genetics, population genetics, clinical genetics, molecular genetics, molecular epidemiology, statistical genetics, genomics, bioinformatics—each from its own perspective. Many other basic and clinical sciences—biochemistry, pathology, and physiology, for example—also contribute. A complete understanding of the etiology of disease requires an interdisciplinary approach drawing on all these fields.